2001
DOI: 10.1088/0264-9381/18/7/306
|View full text |Cite
|
Sign up to set email alerts
|

Holonomy in the Schwarzschild-Droste geometry

Abstract: Parallel transport of vectors in curved spacetimes generally results in a deficit angle between the directions of the initial and final vectors. We examine such holonomy in the Schwarzschild-Droste geometry and find a number of interesting features that are not widely known. For example, parallel transport around circular orbits results in a quantized band structure of holonomy invariance. We also examine radial holonomy and extend the analysis to spinors and to the Reissner-Nordström metric, where we find qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
50
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 23 publications
(41 reference statements)
5
50
0
Order By: Relevance
“…Recently, Rothman, Ellis and Murugan [5] studied some particular curves when a vector A is parallel transported in the geometry of Reissner-Nordströn and then observed very interesting properties of parallel transport that they denominated invariance band holonomy. In this section we analyze the band holonomy properties from the point of view of the parallel transport equation in the background of the rotating black string.…”
Section: Study Of Some Special Orbitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Rothman, Ellis and Murugan [5] studied some particular curves when a vector A is parallel transported in the geometry of Reissner-Nordströn and then observed very interesting properties of parallel transport that they denominated invariance band holonomy. In this section we analyze the band holonomy properties from the point of view of the parallel transport equation in the background of the rotating black string.…”
Section: Study Of Some Special Orbitsmentioning
confidence: 99%
“…Using holonomy, Bollini, Giambiagi and Tiomno [4] investigated the Kerr black holes space-times and obtained many properties of this geometry. In a recent article, Rothman, Ellis and Murugan [5] investigated the holonomy in the Drost-Schwarzschild geometry obtaining very interesting results for a class orbits in this space-time. They found that holonomy in this space-time has a "quantization" property denominated band invariance holonomy.…”
Section: Introductionmentioning
confidence: 99%
“…This global property of the manifold can be used as a means of global classification of spacetimes, as pointed out by Rothman et al [6], who investigated the holonomy in the Schwarzschild-Droste geometry. The aim of present article is to investigate the loop variables in FRW spacetime with the objective of studying the global properties of this spacetime.…”
Section: Introductionmentioning
confidence: 99%
“…Using holonomy, Bollini, Giambiagi and Tiomno [5] investigated the Kerr black hole space-time and obtained many properties of this geometry. In a recent article, Rothman, Ellis and Murugan [6] investigated holonomy in the Schwarzschild-Droste geometry obtaining very interesting results for a class orbits in this space-time. They found that holonomy in this space-time has a "quantization" property denominated band invariance holonomy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation